Bear despair - Dorémus, Gaëtan, 1976- (New York : Enchanted Lion Books, 2012)
A bear gobbles up a wolf, a lion, and an elephant after each animal steals the bear's teddy bear and refuses to return it.
Translation of: Chagrin d'ours.
Keywords: Teddy bears -- Juvenile fiction; Animals -- Juvenile fiction; Animals; Teddy bears; Stories without words; Animals -- Juvenile fiction; Animals -- Fiction; Stories without words; Fiction. -- Animals; Fiction. -- Teddy bears; Picture books; Fiction; Juvenile works; Stories without words; Stories without words -- Juvenile; Picture books; Stories without words